2017
DOI: 10.1056/nejmoa1600869
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery versus Intensive Medical Therapy for Diabetes — 5-Year Outcomes

Abstract: BACKGROUND Long-term results from randomized, controlled trials that compare medical therapy with surgical therapy in patients with type 2 diabetes are limited. METHODS We assessed outcomes 5 years after 150 patients who had type 2 diabetes and a body-mass index (BMI; the weight in kilograms divided by the square of the height in meters) of 27 to 43 were randomly assigned to receive intensive medical therapy alone or intensive medical therapy plus Roux-en-Y gastric bypass or sleeve gastrectomy. The primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

68
1,439
5
66

Year Published

2017
2017
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,138 publications
(1,674 citation statements)
references
References 24 publications
68
1,439
5
66
Order By: Relevance
“…However, the median disease-free period among such individuals following Roux-en-Y gastric bypass (RYGB) is 8.3 years (52,53). With or without diabetes relapse, the majority of patients who undergo surgery maintain substantial improvement of glycemic control from baseline for at least 5 (54,55) to 15 (38,39,53,(56)(57)(58) years.…”
mentioning
confidence: 99%
“…However, the median disease-free period among such individuals following Roux-en-Y gastric bypass (RYGB) is 8.3 years (52,53). With or without diabetes relapse, the majority of patients who undergo surgery maintain substantial improvement of glycemic control from baseline for at least 5 (54,55) to 15 (38,39,53,(56)(57)(58) years.…”
mentioning
confidence: 99%
“…These differences were achieved within only 3 months after treatment, and are durable, having been observed in both a 3-year and 5-year follow-up. 13,19 The SOS study comparing surgical and medical weight loss found that the surgical group had significantly greater weight loss and had lower overall mortality. 20 Similar to the STAMPEDE study, weight loss occurs almost immediately after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a significant decrease in insulin levels and fasting blood glucose postoperatively [10]. According a recent study, having bariatric surgery being done in addition to intensive medical therapy for the treatment of type 2 diabetes in patients with BMI 27-43, yielded significant results in the reduction and sometimes resolving of diabetes compared to intensive medical therapy alone [12]. Another recent study showed that the risk of microvascular complications is reduced due to improved glycemic control in pre diabetic patients who undergo bariatric surgery [13].…”
Section: Discussionmentioning
confidence: 99%